Parent, Teacher, and Student Perceptions of Conjoint Behavioral Consultation for Middle School Students. Issue 4 (2nd October 2022) - Garbacz, S. Andrew; Jordan, Phoebe; Novotnak, Tanya; Young, Kaitlyn; Zahn, Miranda; Markham, Mitchell A.
ABSTRACT: The purpose of this study was to obtain perspectives of parents, teachers, and students about the contextual fit of conjoint behavioral consultation for supporting middle school students with emotional and behavior concerns. Participants were eight parents of middle school students with elevated behavior risk, eight middle school students with elevated behavior risk, and four middle school general education teachers. Participants responded to questions during focus groups and interviews regarding their perspectives about conjoint behavioral consultation. Results were analyzed using thematic coding to identify the themes from participant responses. Results suggested that parents, teachers, and students viewed aspects of CBC as relevant and useful. In addition, participants identified potential barriers to CBC implementation during middle school. Findings suggest implications for possible modifications to enhance CBC implementation during middle school. Limitations and future research directions are discussed.